ZigBee Technology: A Comprehensive Review of Protocol, Applications, and Advancements - Yash Paul,; Rajesh Singh, (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Networks are constantly stepping out for different applications. Among the most well-known transceiver protocols for networks of wireless sensors is ZigBee. ZigBee defines the low power monitoring and controlling devices in the Low data rate WPAN (LR-WPAN) specifications over IEEE 802.15.4. Being different from various existing technologies for wireless sensor networks, ZigBee protocol standard is noticed due to its exceptional features and short range. Besides encouraging the growth of wireless personal area networks, this technology is becoming increasingly vital in daily life. Zigbee is an ad hoc wireless network technology that is low-power, low-data-rate, and short-distance (also known as personal area networks) according to the authors of this research. It was developed as an open global standard to serve the special needs of inexpensive and low-power wireless IoT networks. It is based on the IEEE 802.15.4 specification for a suite of high level communication protocols.